2017
DOI: 10.1016/j.resp.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic A1/C1 neurons contribute to the maintenance of upper airway muscle tone but may not participate in NREM sleep-related depression of these muscles

Abstract: Neural mechanisms of obstructive sleep apnea, a common sleep-related breathing disorder, are incompletely understood. Hypoglossal motoneurons, which provide tonic and inspiratory activation of genioglossus (GG) muscle (a major upper airway dilator), receive catecholaminergic input from medullary A1/C1 neurons. We aimed to determine the contribution of A1/C1 neurons in control of GG muscle during sleep and wakefulness. To do so, we placed injections of a viral vector into DBH-cre mice to selectively express the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 80 publications
2
14
0
Order By: Relevance
“…Neurons in the pre-Botzinger complex, which are responsible for generating respiratory rhythms, experience vesicle accumulation in the somas of Gaa −/− but not WT mice [44]. Neurons in the A1/C1 group, which are speculated to modulate and activate breathing, especially during hypoxia, also have abnormal morphology and vesicle accumulation in Gaa −/− but not WT mice [44,68,69].…”
Section: Additional Neural Control Centersmentioning
confidence: 99%
“…Neurons in the pre-Botzinger complex, which are responsible for generating respiratory rhythms, experience vesicle accumulation in the somas of Gaa −/− but not WT mice [44]. Neurons in the A1/C1 group, which are speculated to modulate and activate breathing, especially during hypoxia, also have abnormal morphology and vesicle accumulation in Gaa −/− but not WT mice [44,68,69].…”
Section: Additional Neural Control Centersmentioning
confidence: 99%
“…Neurons in the pre-Botzinger complex, which are responsible for generating respiratory rhythms, experience vesicle accumulation in the somas of Gaa -/-but not WT mice [41]. Neurons in the A1/C1 group, which are speculated to modulate and activate breathing especially during hypoxia, also have abnormal morphology and vesicle accumulation in Gaa -/-but not WT mice [41,64,65].…”
Section: Additional Neural Control Centersmentioning
confidence: 99%
“…However theoretically, there is a possibility that the release of noradrenaline from A1 terminals within the hypoglossal nucleus is modulated through some sleep-specific presynaptic inhibitory mechanisms, similar to the discovered earlier, presynaptic cholinergic control of glutamate release to hypoglossal motoneurons ( 62 ). To this end, we recently tested the role of medullary A1/C1 neurons in control of the activity of genioglossus muscle using the “designer receptor exclusively activated by a designer drug” (DREADD) technique ( 77 ). A Cre-dependent viral vector hSyn-Dio-hM4Di-mCherry-AAV10 was microinjected into the A1/C1 region, which resulted in the expression of inhibitory receptors in the A1/C1 neurons in behaving dopamine β-hydroxylase (DBH)-cre mice, in which the Cre-recombinase is expressed in all catecholaminergic neurons.…”
Section: Neurotransmitters Implicated In the Control Of Hypoglossal Mmentioning
confidence: 99%
“…This suggested that A1/C1 neurons provide a net excitatory effect on the activity of upper airway muscles. However, the relative effect of CNO on the genioglossus activity was similar during both wakefulness and NREM sleep suggesting that A1/C1 neurons do not contribute to depression of genioglossus activity during transition from wakefulness to NREM sleep ( 77 ).…”
Section: Neurotransmitters Implicated In the Control Of Hypoglossal Mmentioning
confidence: 99%